Background to fusion: Natal, 1932-1933 : correspondence between Smuts and Heaton Nicholls (Historia, 2021)
Fusion between General Smuts and Hertzog was preceded by a great deal of delicate diplomacy between the two generals. It was well known that Dr. Malan and his group were not in favour of joining the South African Party, and a good few South African Party members felt the same about joining the Nationalists. Mrs. M. Jansen formulated the feelings of the Malan group as follows: "There are elements in the South African Party to whom we can extend the hand of brotherhood, but there are elements with whom I, as an Afrikaner woman, cannot associate".l Mr. Leslie Blackwell issued a statement in Cape Town on the 7th June, 1934, in which he stated: ". . . for me at any rate there is no fusion if the new party includes Dr. Malan and his followers. Mr. Erasmus and I can never lie under the same political blanket."
Keywords: Heaton Nicholls; Politics; Political parties; General Smuts; General Hertzog; Natal